Predictors and Impact of Arts Engagement During the COVID-19 Pandemic: Analyses of Data From 19,384 Adults in the COVID-19 Social Study - Mak, Hei Wan; Fluharty, Meg; Fancourt, Daisy (Frontiers in Psychology, 2021)
Objectives. The global COVID-19 pandemic in 2020 heavily affected the arts and creative industries due to the instigation of lockdown measures in the UK and closure of venues. However, it also provided new opportunities for arts and cultural engagement through virtual activities and streamed performances. Yet it remains unclear (i) who was likely to engage with the arts at home during lockdown, (ii) how this engagement differed from patterns of arts engagement prior to COVID-19, and (iii) whether home-based arts engagement was related to people’s ability to cope with their emotions during lockdown. This study was therefore designed to address these questions. Methods. We used data collected in late May from the UK COVID-19 Social Study run by University College London. Multivariate regressions were used for the analysis (N=19,384). Identified factors included demographic factors, socio-economic position, psychosocial wellbeing and health conditions, adverse events/worries, and coping styles. Results. Four types of home-based arts engagement were identified during the COVID-19 pandemic: digital arts & writing, musical activities, crafts, and reading for pleasure. Our results show that the strongest predictors of the engagement were age, education attainment, social support, and emotion-focused or supportive coping styles. In particular, younger adults (aged 18-29), non-keyworkers, people with greater social support, people who had lost work, those who were worried about catching the virus, and those with an emotion-focused, problem-focused or supportive coping style were more likely to have increased arts engagement during lockdown. Arts activities were used as approach and avoidance strategies to help cope with emotions, as well as to help improve self-development. Conclusions. Overall, our study suggests that while some people who engaged in the arts during the COVID-19 pandemic were those who typically engage under normal circumstances, the pandemic has also created new incentives and opportunities for others to engage virtually. Additionally, this study highlights the value of the arts as coping tools during stressful situations.